Mangrove Ecosystem Service Values and Methodological Approaches to Valuation: Where Do We Stand? - Himes-Cornell, Amber; Grose, Susan O.; Pendleton, Linwood (Frontiers in Marine Science, 2018)
Mangroves, seagrass meadows, and salt marshes, collectively termed “Blue Forests”, are counted among the most valuable and productive coastal ecosystems on the planet. A recent literature review of the Blue Forest valuation research identified mangroves as the most frequently analyzed of these ecosystems, yet the literature demonstrates several deficits in terms of geographic location of studies, methods used to value the services, and most notably, a lack of valuation for cultural services. To better understand this, we analyzed the studies dealing specifically with mangroves from the original literature review to quantify what has been valued, where, by which methods, and the variation in the published values. We then use this information to synthesize our current level of knowledge on the type and value of services provided by mangroves, discuss data gaps, and address specifically the collection of data relevant to cultural ecosystem services (CES). Our results shed light on two principle issues affecting the mangrove valuation literature: overuse of benefit transfer in valuing mangrove ecosystem services and a lack of attention paid to the CES that mangroves provide. The mangrove valuation literature is not yet robust, lacking estimates of many ecosystem services, including CES, such as spiritual and aesthetic value. Most published studies focus on a small selection of ecosystem services based on the availability of benefit transfer values and the ability to easily measure values with market prices. Thus, many ecosystem services that cannot be valued monetarily, but that are often equally important to local communities, are ignored. Given the wide range of ecosystem services mangroves provide and the variety of valuation methods that need to be collectively employed, we argue that doing valuation studies well requires a multi-disciplinary approach, bringing together anthropologists, social scientists, ecologists and economists. Thoughtfully and thoroughly including the local stakeholders in valuation studies and the resultant policy discussions leads to a more holistic understanding of the services mangroves provide, and viable solutions with an increase in local willingness to act in accordance with those solutions.